Plasmonic layers based on Au-nanoparticle-doped TiO2 for optoelectronics: structural and optical properties - Pedrueza, E; Sancho-Parramon, J; Bosch, S; Valdés, J L; Martinez-Pastor, J P (Nanotechnology, 2013)
The anti-reflective effect of dielectric coatings used in silicon solar cells has traditionally been the subject of intensive studies and practical applications. In recent years the interest has permanently grown in plasmonic layers based on metal nanoparticles, which are shown to increase light trapping in the underlying silicon. In the present work we have combined these two concepts by means of in situ synthesis of Au nanoparticles in a dielectric matrix (TiO2), which is commonly used as an anti-reflective coating in silicon solar cells, and added the third element: a 10-20% porosity in the matrix. The porosity is formed by means of a controllable wet etching by low concentration HF. As a consequence, the experimentally measured reflectance of silicon coated by such a plasmonic layer decreases to practically zero in a broad wavelength region around the localized surface plasmon resonance. Furthermore, we demonstrate that extinction and reflectance spectra of silicon coated by the plasmonic films can be successfully accounted for by means of Fresnel formulae, in which a double refractive index of the metal-dielectric material is used. This double refractive index cannot be explained by effective medium theory (Maxwell-Garnett, for example) and appears when the contribution of Au nanoparticles located at the TiO2/Si interface is high enough to result in formation of interface surface plasmon modes.